Fe-MOF hydrogel bead phosphorus adsorption material and preparation method thereof

Through the preparation of Fe-MOF hydrogel bead material, the problems of low efficiency and difficulty in recycling of phosphorus removal adsorbents in the prior art are solved, and efficient phosphorus adsorption and recovery are achieved, and the material has good water stability and reusability.

CN119608127APending Publication Date: 2025-03-14HOHAI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510082113.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

It is difficult to develop efficient and economical phosphorus removal adsorbents in the prior art, and it is difficult to achieve phosphorus resource recycling.

Method used

Fe-MOF hydrogel bead material is used to load Fe-MOFs onto the hydrogel, and efficient phosphorus adsorption materials are prepared through ultrasonic dispersion, water bath heating and aging.

Benefits of technology

It realizes efficient phosphorus adsorption and recovery, solves the problem of difficulty in recycling adsorbents, and the material has good water stability and reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608127A_ABST
    Figure CN119608127A_ABST
Patent Text Reader

Abstract

The invention provides a Fe-MOF hydrogel bead phosphorus adsorption material and a preparation method thereof, and belongs to the technical field of adsorption materials. The preparation method comprises the following steps: mixing phthalic acid and ferric nitrate in an N, N-dimethylformamide solution, then carrying out ultrasonic dispersion and centrifugation to collect solid substances, and sequentially drying and grinding the solid substances to obtain a Fe-MOF material; the Fe-MOF material and sodium alginate are mixed in an aqueous solution for water bath heating, and Fe-MOF hydrogel is obtained; the Fe-MOF hydrogel is dropwise added into a CaCl2 solution, and after aging, the Fe-MOF hydrogel bead phosphorus adsorption material is obtained. The Fe-MOFs are loaded on the hydrogel, so that the separation efficiency of the material can be effectively improved, and the problem that the adsorbent is difficult to recover is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a Fe-MOF hydrogel bead phosphorus adsorption material and a preparation method thereof. Background Art

[0002] Phosphorus is an important nutrient element in life activities on Earth and is also a potential non-renewable resource. Developing efficient and economical phosphorus removal adsorbents for phosphorus in wastewater and realizing phosphorus resource recovery are issues that need to be addressed urgently.

[0003] Metal-organic frameworks (MOFs) are formed by the bond coordination of multifunctional organic ligands and metal clusters. MOFs have the characteristics of high crystallinity, adjustable pores, rich active sites, high mechanical and thermal stability, simple synthesis, and excellent performance, and have been widely used in many fields.

[0004] How to obtain an adsorbent material for phosphorus removal is a technical problem that needs to be solved at present. Summary of the invention

[0005] The object of the present invention is to provide a Fe-MOF hydrogel bead phosphorus adsorption material and a preparation method thereof, so as to solve the technical problem of phosphorus adsorption.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a Fe-MOF hydrogel bead phosphorus adsorption material, comprising the following steps:

[0008] 1) mixing phthalic acid and ferric nitrate in an N,N-dimethylformamide solution, then ultrasonically dispersing and centrifuging to collect solid matter, and then drying and grinding the solid matter in sequence to obtain a Fe-MOF material;

[0009] 2) mixing the Fe-MOF material and sodium alginate in an aqueous solution and heating the mixture in a water bath to obtain a Fe-MOF hydrogel;

[0010] 3) The Fe-MOF hydrogel is added dropwise into a CaCl2 solution, and after aging, the Fe-MOF hydrogel bead phosphorus adsorption material is obtained.

[0011] Furthermore, the concentration of the ferric nitrate in the N,N-dimethylformamide solution is 0.5-1.5 mol / L, and the concentration of the phthalic acid in the N,N-dimethylformamide solution is 0.2-0.8 mol / L.

[0012] Furthermore, the drying temperature is 50-80°C.

[0013] Furthermore, the mass ratio of the Fe-MOF material to sodium alginate is 1:1-10, the water bath heating temperature is 35-55° C., the water bath heating time is 30-60 min, and stirring is continued for 6-12 h after stopping the water bath heating.

[0014] Furthermore, the dropping is performed by a peristaltic pump, the flow rate of the liquid in the peristaltic pump is 30 to 150 mL / min, and the height of the liquid outlet of the peristaltic pump from the liquid level of the CaCl2 solution is 15 to 25 cm.

[0015] Furthermore, the aging time is 8 to 24 hours.

[0016] The invention also provides a Fe-MOF hydrogel bead phosphorus adsorption material.

[0017] Beneficial effects of the present invention:

[0018] The present invention uses a rigid organic ligand terephthalic acid to synthesize MOFs materials with higher water stability than other flexible ligands, and can better maintain a porous structure when adsorbing phosphorus in water. Iron has little negative effect on the environment, is relatively cheap and has good chemical stability, and has a strong affinity and high selectivity with phosphates. Therefore, iron and terephthalic acid are synthesized by coordination Fe-MOFs for the adsorption and separation of phosphorus. Hydrogel materials have irreplaceable advantages in the fields of environmental remediation and pollution control, good reusability, and high recovery rate. By loading Fe-MOFs onto hydrogels, the separation efficiency of the material can be effectively improved, solving the problem of difficult adsorbent recovery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a curve diagram of the removal rate of phosphorus in lakes by the Fe-MOF hydrogel bead phosphorus adsorption material in Example 4 of the present invention. DETAILED DESCRIPTION

[0020] The present invention provides a method for preparing a Fe-MOF hydrogel bead phosphorus adsorption material, comprising the following steps:

[0021] 1) mixing phthalic acid and ferric nitrate in an N,N-dimethylformamide solution, then ultrasonically dispersing and centrifuging to collect solid matter, and then drying and grinding the solid matter in sequence to obtain a Fe-MOF material;

[0022] 2) mixing the Fe-MOF material and sodium alginate in an aqueous solution and heating the mixture in a water bath to obtain a Fe-MOF hydrogel;

[0023] 3) The Fe-MOF hydrogel is added dropwise into a CaCl2 solution, and after aging, the Fe-MOF hydrogel bead phosphorus adsorption material is obtained.

[0024] In the present invention, the concentration of the ferric nitrate in the N,N-dimethylformamide solution is 0.5-1.5 mol / L, preferably 0.8-1.2 mol / L, and more preferably 1.0 mol / L; the concentration of the phthalic acid in the N,N-dimethylformamide solution is 0.2-0.8 mol / L, preferably 0.3-0.7 mol / L, and more preferably 0.4-0.6 mol / L.

[0025] In the present invention, the drying temperature is 50 to 80°C, preferably 60 to 70°C, and more preferably 65°C.

[0026] In the present invention, the mass ratio of the Fe-MOF material to sodium alginate is 1:1-10, preferably 1:2-9, and more preferably 1:3-8; the water bath heating temperature is 35-55°C, preferably 40-50°C, and more preferably 45°C; the water bath heating time is 30-60min, preferably 40-50min, and more preferably 45min; after stopping the water bath heating, stirring is continued for 6-12h, preferably 7-10h, and more preferably 8-9h.

[0027] In the present invention, the dripping is carried out by a peristaltic pump, the flow rate of the liquid in the peristaltic pump is 30 to 150 mL / min, preferably 50 to 120 mL / min, and further preferably 60 to 100 mL / min; the height of the liquid outlet of the peristaltic pump from the liquid level of the CaCl2 solution is 15 to 25 cm, preferably 20 cm.

[0028] In the present invention, the aging time is 8 to 24 hours, preferably 10 to 20 hours, and more preferably 12 to 18 hours.

[0029] The invention also provides a Fe-MOF hydrogel bead phosphorus adsorption material.

[0030] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0031] Example 1

[0032] Preparation of Fe-MOF materials

[0033] 1) Mix Fe(NO3)3·9H2O and terephthalic acid and add them into N,N-dimethylformamide solution and stir for 12 hours;

[0034] 2) After ultrasonic dispersion of the reactant in step 1), the solid matter was collected by centrifugation, vacuum dried at 60° C., ground into uniform particles and passed through a 300-mesh sieve to obtain a Fe-MOF material;

[0035] The material prepared in this embodiment is in the form of a yellow-brown powder, wherein in step 1), the concentration of terephthalic acid is 0.3 mol / L, the concentrations of the Fe(NO3)3·9H2O solutions are 0.5, 0.75, 1.0, 1.25 and 1.5 mol / L, respectively, and the obtained Fe-MOF materials are recorded as: 0.5Fe-MOF, 0.75Fe-MOF, 1.0Fe-MOF, 1.25Fe-MOF, 1.5Fe-MOF, respectively.

[0036] 0.2 g of Fe-MOF material was placed in a 150 mL conical flask, dispersed in 100 mL of KH2PO4 (10 mg / L) solution, placed in a constant temperature oscillator at 25 °C and oscillated at 200 rpm for 1 h. The adsorption effect on phosphorus was measured. The results are shown in Table 1.

[0037] The content of KH2PO4 was determined by using an ultraviolet spectrophotometer according to the ammonium molybdate spectrophotometric method.

[0038] Table 1 Adsorption effect of Fe-MOF materials on phosphorus

[0039] synthetic materials Ferric nitrate concentration (mol / L) Phosphate adsorption rate (%) 0.5Fe-MOF 0.5 98.35 0.75Fe-MOF 0.75 98.43 1.0Fe-MOF 1.0 98.67 1.25Fe-MOF 1.25 99.01 1.5Fe-MOF 1.5 99.11

[0040] Example 2

[0041] Preparation of Fe-MOF hydrogel beads with different ratios of phosphorus adsorption materials

[0042] 1) Prepare a solution of Fe(NO3)3·9H2O and terephthalic acid in N,N-dimethylformamide, and stir it for 12 hours, wherein the iron nitrate is 0.5 mol / L and the terephthalic acid is 0.3 mol / L.

[0043] 2) The liquid obtained in step 1) is dispersed by ultrasonication, and the solid matter is collected by centrifugation, and then vacuum dried at 60° C., ground into particles, and passed through a 300-mesh sieve to obtain a Fe-MOF material;

[0044] 3) adding the Fe-MOF material obtained in step 2) and sodium alginate into the aqueous solution in a certain ratio (1 / 10, 1 / 7, 1 / 5, 1 / 3, 1 / 1), stirring evenly, and obtaining Fe-MOF hydrogel;

[0045] 4) The Fe-MOF hydrogel obtained in step 3) is added dropwise to the CaCl2 solution through a peristaltic pump, and after aging, the Fe-MOF hydrogel bead phosphorus adsorption material is obtained. The flow rate of the peristaltic pump is 30 ml / min, and the height of the peristaltic pump liquid outlet from the CaCl2 solution liquid level is 20 cm; the aging time is 8 hours. The obtained Fe-MOF hydrogel bead phosphorus adsorption materials are recorded as 0.5Fe-MOF / SA-1 / 10, 0.5Fe-MOF / SA-1 / 7, 0.5Fe-MOF / SA-1 / 5, 0.5Fe-MOF / SA-1 / 3, and 0.5Fe-MOF / SA-1 / 1.

[0046] The phosphorus adsorption effects of the Fe-MOF hydrogel bead phosphorus adsorption materials prepared in different proportions in this example are shown in Table 2, and the determination method is the same as that in Example 1.

[0047] Table 2 Phosphorus adsorption effect of different proportions of Fe-MOF hydrogel beads phosphorus adsorption materials

[0048] Synthetic material name Fe-MOF / sodium alginate Phosphate adsorption rate (%) 0.5Fe-MOF / SA-1 / 10 1 / 10 98.35 0.5Fe-MOF / SA-1 / 7 1 / 7 99.12 0.5Fe-MOF / SA-1 / 5 1 / 5 98.56 0.5Fe-MOF / SA-1 / 3 1 / 3 98.32 0.5Fe-MOF / SA-1 / 1 1 / 1 97.78

[0049] Under the same conditions, 0.5Fe-MOF / SA-1 / 7 showed better adsorption performance, with a phosphorus recovery rate of 99.12%. The preparation of hydrogel beads can reduce the use of Fe-MOF materials, and the hydrogel beads are small balls with a diameter of about 4 mm, which are very easy to recycle.

[0050] Example 3

[0051] Preparation of Fe-MOF hydrogel beads with different particle sizes for phosphorus adsorption

[0052] 1) Prepare a solution of Fe(NO3)3·9H2O and terephthalic acid in N,N-dimethylformamide, and stir it for 12 hours, wherein the Fe(NO3)3·9H2O is 0.5 mol / L and the terephthalic acid is 0.3 mol / L.

[0053] 2) The liquid obtained in step 1 is dispersed by ultrasonication, and the solid matter is collected by centrifugation, and then vacuum dried at 60° C., ground into particles, and passed through a 300-mesh sieve to obtain a Fe-MOF material;

[0054] 3) adding the Fe-MOF material obtained in step 2 and sodium alginate into the aqueous solution at a ratio of 1 / 7 and stirring evenly to obtain Fe-MOF hydrogel;

[0055] 4) The Fe-MOF hydrogel obtained in step 3 is added dropwise to the CaCl2 solution through a peristaltic pump, and after aging, the Fe-MOF hydrogel bead phosphorus adsorption material is obtained. The flow rate of the peristaltic pump is 30, 90, and 150 ml / min, and the height of the peristaltic pump liquid outlet from the CaCl2 solution level is 15, 20, and 25 cm; the aging time is 8 hours.

[0056] The phosphorus adsorption effects of the Fe-MOF hydrogel beads phosphorus adsorption materials with different particle sizes prepared in this example are shown in Table 3, and the determination method is the same as that in Example 1.

[0057] Table 3 Phosphorus adsorption effect of Fe-MOF hydrogel beads with different particle sizes

[0058]

[0059]

[0060] As the particle size gradually decreases, the phosphorus adsorption performance of Fe-MOF hydrogel beads gradually increases. This shows that the composite material with small particle size has good dispersibility and is more likely to adsorb surrounding phosphate ions.

[0061] Example 4

[0062] Adsorption and recovery of phosphorus in lakes by adding different Fe-MOF hydrogel beads phosphorus adsorption materials.

[0063] Take lake water with an initial phosphorus concentration of 6.38 mg / L, and the dosage range of adsorbent 0.5Fe-MOF / SA-1 / 7 is 0.05~1g / L. The phosphorus concentration of the lake water after adsorption is immediately measured, such as Figure 1 When the adsorbent dosage exceeds 0.15 g / L, more than 90% of the phosphate in the lake water can be removed, and the phosphate concentration can be reduced to below 0.23 mg / L within 1 hour.

[0064] Comparative Example 1

[0065] 1) Prepare Fe(NO3)3·9H2O and terephthalic acid, add them into N,N-dimethylformamide solution, and stir for 12 hours;

[0066] 2) After ultrasonically dispersing the reactants in step 1), the solid matter was collected by centrifugation, dried in vacuo at 60° C., ground into uniform particles and passed through a 300-mesh sieve to obtain Fe-MOF powder;

[0067] The material prepared in this embodiment is in the form of yellow-brown powder, wherein in step 1), the concentrations of terephthalic acid are 0.05, 0.1, 0.15, 0.2 and 0.3 mol / L, respectively, the concentration of Fe(NO3)3·9H2O solution is 0.5 mol / L, and the obtained materials are respectively recorded as: 0.5Fe-MOF-0.05, 0.5Fe-MOF-0.1, 0.5Fe-MOF-0.15, 0.5Fe-MOF-0.2, 0.5Fe-MOF-0.3.

[0068] 0.2 g of Fe-MOF adsorbent was placed in a 150 mL conical flask, dispersed in 100 mL of KH2PO4 (10 mg / L) solution, placed in a constant temperature oscillator at 25 °C and oscillated at 200 rpm for 1 h. The adsorption effect on phosphorus was measured. The results are shown in Table 4.

[0069] The content of KH2PO4 was determined by using an ultraviolet spectrophotometer according to the ammonium molybdate spectrophotometric method.

[0070] Table 4 Adsorption effect of Fe-MOF adsorption materials on phosphorus

[0071]

[0072] By comparison, it was found that when the concentration of terephthalic acid increased from 0.05 to 0.3 mg / L, the phosphorus adsorption effect became better and better, and the phosphate adsorption rate increased from 77.23% to 98.35%. However, when the concentration of terephthalic acid was lower than 0.2 mg / L, the phosphate adsorption rate was lower than 95%.

[0073] As can be seen from the above examples, the present invention provides a Fe-MOF hydrogel bead phosphorus adsorption material and a preparation method thereof. The present invention can effectively improve the separation efficiency of the material and solve the problem of difficult adsorbent recovery by loading Fe-MOFs onto the hydrogel.

[0074] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a Fe-MOF hydrogel bead phosphorus adsorption material, characterized in that: The following steps are involved: 1) mixing phthalic acid and ferric nitrate in an N,N-dimethylformamide solution, then ultrasonically dispersing and centrifuging to collect solid matter, and then drying and grinding the solid matter in sequence to obtain a Fe-MOF material; 2) mixing the Fe-MOF material and sodium alginate in an aqueous solution and heating the mixture in a water bath to obtain a Fe-MOF hydrogel; 3) The Fe-MOF hydrogel is added dropwise into a CaCl2 solution, and after aging, the Fe-MOF hydrogel bead phosphorus adsorption material is obtained.

2. The method for preparing the Fe-MOF hydrogel bead phosphorus adsorption material according to claim 1, characterized in that: The concentration of the ferric nitrate in the N,N-dimethylformamide solution is 0.5-1.5 mol / L, and the concentration of the phthalic acid in the N,N-dimethylformamide solution is 0.2-0.8 mol / L.

3. The method for preparing the Fe-MOF hydrogel bead phosphorus adsorption material according to claim 1 or 2, characterized in that: The drying temperature is 50-80°C.

4. The method for preparing the Fe-MOF hydrogel bead phosphorus adsorption material according to claim 3, characterized in that: The mass ratio of the Fe-MOF material to sodium alginate is 1:1-10, the water bath heating temperature is 35-55° C., the water bath heating time is 30-60 min, and stirring is continued for 6-12 h after stopping the water bath heating.

5. The method for preparing the Fe-MOF hydrogel bead phosphorus adsorption material according to claim 1, characterized in that: The dropping is performed by a peristaltic pump, the flow rate of the liquid in the peristaltic pump is 30 to 150 mL / min, and the height of the liquid outlet of the peristaltic pump from the liquid level of the CaCl2 solution is 15 to 25 cm.

6. The method for preparing the Fe-MOF hydrogel bead phosphorus adsorption material according to claim 1, 4 or 5, characterized in that: The aging time is 8 to 24 hours.

7. The Fe-MOF hydrogel bead phosphorus adsorption material prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Metal organic framework aerogel as well as preparation method and application thereof

    CN115025762A

  • Adsorbent for efficiently removing ciprofloxacin in water and preparation method thereof

    CN116272893A

  • Collagen / NH2-MIL-101 (Fe) composite hydrogel suitable for drug carrier and preparation method of collagen / NH2-MIL-101 (Fe) composite hydrogel

    CN117899005A

  • Preparation method of spherical MOF material

    CN118206763A

  • Metal organic framework-alginate / polyvinylalcohol adsorbent, method of preparing the same seawater desalination sysem and seawater desalination method

    KR102332434B1